INFLUENCE OF ARTIFICIAL INTELLIGENCE ON EMPLOYMENT ON THE EXAMPLE OF TRANSPORT INDUSTRY OF FRANCE - K. Patris (Вестник университета)
The problem of implementation of artificial intelligence in the employment, on the example of transport industry of France has been considered. The artificial intelligence, opinions of different observers about the future of employment and workplaces due to application of artificial intelligence have been described. The possible scenario of using of artificial intelligence in transport industry of France, particularly with the implementation of automatic vehicles, has been reviewed. Questions such as technical maintenance of equipment and industrial lines, logistics and optimization of traffic flows and data availability also have been raised. The problem of social acceptability has been analyzed, out of sociological surveys of French population.